Journalism and conflict in Indonesia : from reporting violence to promoting peace - Sharp, Steve. (Routledge contemporary Southeast Asia series ;, 2013)
"This book examines, through the case study of Indonesia over recent decades, how the reporting of violence can drive the escalation of violence, and how journalists can alter their reporting practices in order to have the opposite effect and promote peace"--Supplied by publisher.